a)
is conservative if it is the gradient field for some scalar function
. This would require
![(\partial f)/(\partial x) = e^(y + 2z)](https://img.qammunity.org/2023/formulas/mathematics/college/vvrqx2ljttywdmjib5s7okkzkbhl9dmuw5.png)
![(\partial f)/(\partial y) = x \, e^(y + 2z)](https://img.qammunity.org/2023/formulas/mathematics/college/55w94xzyw31gf13vca9bal3vy4o0ep3br8.png)
![(\partial f)/(\partial z) = ax \, e^(y+2z)](https://img.qammunity.org/2023/formulas/mathematics/college/yco0jyn9dw9gv2001spotrh29o9n54g1tt.png)
Integrating both sides of the first equation with respect to
yields
![f(x,y,z) = x \, e^(y + 2z) + g(y, z)](https://img.qammunity.org/2023/formulas/mathematics/college/h9lfewm81t28rf7iiyuiwguqxb3oepjrzn.png)
Differentiate with respect to
:
![(\partial f)/(\partial y) = x \, e^(y + 2z) = x \, e^(y + 2z) + (\partial g)/(\partial y) \implies (\partial g)/(\partial y) = 0 \implies g(y, z) = h(z)](https://img.qammunity.org/2023/formulas/mathematics/college/z2db592uyg1czwbrrcpeozjqo74v9eziuv.png)
Differentiate with respect to
:
![(\partial f)/(\partial z) = ax \, e^(y + 2z) = 2x \, e^(y + 2z) + (dh)/(dz)](https://img.qammunity.org/2023/formulas/mathematics/college/sbi7t7ebxruplad63em11uhaipjs7da72m.png)
We want
to be independent of
and
; we can make them both disappear by picking
.
b) This is the so-called triple product, which has the property
![(7\,\hat\jmath - 4\,\hat k) \cdot \bigg((-2\,\hat\imath+3\,\hat k) * (\hat\imath + 2\,\hat\jmath-\hat k)\bigg) = \det \begin{bmatrix} 0 & 7 & -4 \\ -2 & 0 & 3 \\ 1 & 2 & -1 \end{bmatrix}](https://img.qammunity.org/2023/formulas/mathematics/college/kv0nod82ypt3apz8dlxyq35slurgw6knn6.png)
Computing the determinant is easy with a cofactor expansion along the first column:
![\det \begin{bmatrix} 0 & 7 & -4 \\ -2 & 0 & 3 \\ 1 & 2 & -1 \end{bmatrix} = 2 \det \begin{bmatrix} 7 & -4 \\ 2 & -1 \end{bmatrix} + \det \begin{bmatrix} 7 & -4 \\ 0 & 3 \end{bmatrix} \\\\ = 2 + 21 = \boxed{23}](https://img.qammunity.org/2023/formulas/mathematics/college/kzt6ig2r24ai8r7cng1fiill5637qtpv2b.png)
c) Let
![z = f(x, y) = \frac{2x^2 + 2xy - 1}3](https://img.qammunity.org/2023/formulas/mathematics/college/eectvgb9fvy9gl1eik711lu9rzo8gi52mo.png)
Compute the partial derivatives and evaluate them at
:
![(\partial f)/(\partial x) = \frac{4x + 2y}3 \implies f_x(1,1) = 2](https://img.qammunity.org/2023/formulas/mathematics/college/82cjtup4ayo83hlup3lo3c7f24cdiqkotv.png)
![(\partial f)/(\partial y) = \frac{2x}3 \implies f_y(1,1) = \frac23](https://img.qammunity.org/2023/formulas/mathematics/college/il4d9sb9klgtvloo3x5t2fhxh4fhx288lf.png)
Then the tangent plane to
at (1, 1, 1) has equation
![z - 1 = 2 (x - 1) + \frac23 (y - 1) \implies \boxed{6x + 2y - 3z = 5}](https://img.qammunity.org/2023/formulas/mathematics/college/d45wv0v0mf2a8qrjl46wqzrnp86yzk6i41.png)
d) In polar coordinates,
is the set
![R = \left\{ (r, \theta) ~:~ 0 \le r \le 3 \text{ and } 0 \le \theta \le 2\pi \right\}](https://img.qammunity.org/2023/formulas/mathematics/college/svd0zlo4uuvge12tsid25npipw8mnly3q1.png)
Then the integral evaluates to
![\displaystyle \iint_R (dA)/(\pi√(x^2+y^2)) = \frac1\pi \int_0^(2\pi) \int_0^3 (r\,dr\,d\theta)/(√(r^2)) \\\\ = \frac1\pi \left(\int_0^(2\pi)d\theta\right) \left(\int_0^3dr\right) = 2*3 = \boxed{6}](https://img.qammunity.org/2023/formulas/mathematics/college/44dvqlng55qbp6rbvm6xn9new16kqa7o36.png)
e) By the chain rule,
![(\partial w)/(\partial t) = (\partial w)/(\partial x) (\partial x)/(\partial t) + (\partial w)/(\partial y) (\partial y)/(\partial t)](https://img.qammunity.org/2023/formulas/mathematics/college/nrwsd7tb610bj8xrzbsc9ln0r3nwhprcu7.png)
Eliminating the parameter, we find
![(x + y^2) - (3x + y) = t - t \implies x = \frac{y^2 - y}2](https://img.qammunity.org/2023/formulas/mathematics/college/3z5dxdqoursakmqcbsjvkrg1vr530joua9.png)
so that
when
.
Compute derivatives:
![(\partial w)/(\partial x) = 14x^(13)](https://img.qammunity.org/2023/formulas/mathematics/college/wsii2ek9fje5j4klbbzt2f0ac6ogrr8bvc.png)
![(\partial w)/(\partial y) = 1](https://img.qammunity.org/2023/formulas/mathematics/college/6sy01hkgee2lubwe6p9uoeup8iuwtvph1n.png)
![\begin{cases} x + y^2 = t \\ 3x + y = t \end{cases} \implies \begin{cases}(\partial x)/(\partial t) + 2y (\partial y)/(\partial t) = 1 \\\\ 3 (\partial x)/(\partial t) + (\partial y)/(\partial t) = 1 \end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/t87iubyahj5onn8w1dr9cm4e9hwy3r2uet.png)
![\left((\partial x)/(\partial t) + 2y(\partial y)/(\partial t)\right) - 2y \left(3(\partial x)/(\partial t) + (\partial y)/(\partial t)\right) = 1 - 2y \implies (\partial x)/(\partial t) = (2y-1)/(6y-1)](https://img.qammunity.org/2023/formulas/mathematics/college/i7yl5w3ptr736fvdtc8k6eosj312u7gsra.png)
![3\left((\partial x)/(\partial t) + 2y (\partial y)/(\partial t)\right) - \left(3(\partial x)/(\partial t) + (\partial y)/(\partial t)\right) = 3 - 1 \implies (\partial y)/(\partial t) = \frac2{6y-1}](https://img.qammunity.org/2023/formulas/mathematics/college/eq57gj92dwmicdlbk3ghdst7rgnsqv5nfv.png)
Then at the point (1, 1), the derivative we want is
![(\partial w)/(\partial t) = 14 *\frac3{11} + \frac2{11} = (44)/(11) = \boxed{4}](https://img.qammunity.org/2023/formulas/mathematics/college/amw1lhdp1lxw9nch5a2zlpvjcw3w7z523j.png)